The Traveller as a Translator: Intralingual Translation in Brazilian Road Films - Helou Chubaci Guercio, Nayara (Trinity College (Dublin, Ireland). School of Languages, Literature and Cultural Studies, 2020)
This dissertation aims at answering the following question: what are the visual and thematic choices in the representation of intralingual translation in Brazilian cinematic travel narratives? The corpus of analysis is comprised by the films: Central Station (Water Salles, 1998) and Cinema, Aspirins and Vultures (Marcelo Gomes, 2005). This study hopes to continue the research developed in the books Translation Goes to the Movies (Cronin 2009) and Across the Lines: Travel, Language, Translation (Cronin 2000). This research subscribes to the logical system of deduction and it is categorised as a basic empirical study. The materials used are from bibliographical and audiovisual sources. The chosen method of analysis is an interpretation of Casetti & Di Chio’s (1998: 126) methodological proposal for analysing the filmic text, which are: isolation, identification and interpretation. The categories of analysis are Cronin’s (2006: 131) three levels in which intralingual translation can occur. After the analysis, it is concluded that the thematic choices in the representation of intralingual translation in Brazilian cinematic travel narratives revolve around: 1) the effects of intralingual translation in each of the travellers’ identities; 2) the role of intralingual translation in the relationship forged between the two travellers and; 3) the role of intralingual translation in the relationship forged between the travellers and other characters. In order to showcase the three themes, the visual choices in both films mostly rely on editing and frame composition. Symmetry proved to be the most relevant aspect to both. Soundtrack, however, is not as fundamental in Cinema, Aspirins and Vultures (Marcelo Gomes, 2005) as it is in Central Station (Walter Salles, 1998). The findings in this research reinforce that translation studies, film studies and the study of travel narratives can benefit from one another as fields of research.
Keywords: Literary Translation